Polymer composite Belleville springs for an automotive application. (1st August 2019) - Foard, J.H.D.; Rollason, D.; Thite, A.N.; Bell, C.
Abstract: This paper investigates mathematical modelling and manufacturing of polymer composite Belleville springs, and their potential application. The original expression for load carrying capacity developed for metal springs is refined by considering the variation of elastic modulus and Poisson's ratio of laminates in polar coordinates. A novel series spring stacking arrangement is proposed to achieve complex stiffness variation by progressive action. The experimental results show consistent effect of number of plies on the spring rate and compare well with the theoretical predictions. Although handmade, the variations in load carrying capacity is very small (∼10%) confirming manufacturing viability. It is shown that a smooth, variable spring rate curve can be produced by reducing slip-stick frictional forces with the use of spacers within the spring stacks. In one application, the composite springs are shown to offer significant vehicle dynamic performance improvement through reduction of the tyre contact patch force variation and vehicle body acceleration.